Compared to without video assistant referee: does video assistant referee monitoring have an impact on the Chinese Super League? - Zhang, B.; Lin, M.; Qi, D.; Zhang, L.; Deng, P. (BMC Sports Science, Medicine and Rehabilitation, 2025)
Background Even though the Chinese Super League (CSL) introduced Video Assistant Referees (VARs) in the 2018 season, it did not intervene in every game. The Hawthorne effect highlights how human behavior can change when individuals are aware they are being observed. VARs monitoring means VARs just introduces but does not intervene in the games. Thus, this research compared the performance in the games where VARs did not intervene and without VARs, to investigate whether VARs monitoring influences match performance, similar to the Hawthorne effect.